Modeling and Optimization of Refrigeration Systems - Ahmadi, Pouria; Dincer, Ibrahim; Rosen, Marc A (Optimization of Energy Systems, 2017)
This chapter first describes refrigeration cycles and their energy and exergy analyses, and to model comprehensively and optimize selected refrigeration systems. It then defines objective function(s) and, usually, applying multi‐objective optimization to determine the best optimal design parameters of the system. In order to enhance understanding of the design criteria, a sensitivity analysis is conducted to assess how each objective function varies when design parameters are varied. Two objective functions are considered for multi‐objective optimization: system exergy efficiency and total cost rate. The decision variables (design parameters) in this optimization are evaporator temperature (T eva ), condenser temperature (T cond ), evaporator pinch point temperature (PPTD 1 ), condenser pinch point temperature (PPTD 2 ), and compressor isentropic efficiency (η comp ). Optimization can help refrigeration engineers determine the best operation point of a refrigeration system subject to constraints, and is applied to the absorption chiller.